“An Analysis of Investment Pattern of People During the period of 2018-19 in Surat City” - Sabhaya, Ranjan Jaykant (International Journal of Psychosocial Rehabilitation, 2020)
Investments come from savings and savings is a portion of Total Income. If person has good income, ones can have good amount of savings which may lead to good investment. Present income level defines the present living standard and investment defines future living standard. Indian government has been always trying to push up the public for savings and investment for the development of the economy. In the country, people have certain trends to invest in certain direction. Investment pattern is the investment in different investment avenues with vital consideration of risk and return.This research has been conducted to analyze the investment pattern of people in Surat City during the period of 2018-19. This research is based on primary data. A survey of 203 investors in Surat city has been conducted to draw the conclusion. There are lot many options for the investments but this research has considered only most preferable investment avenues by the public of Surat City like Mutual Funds, Equity, Insurance, Bonds, Gold, Real Estate and Bank Deposits to find out the investment pattern.To analyze the data, hypothesis has been developed and appropriate tests have been applied. According to the Survey and Data Analysis, most preferred Investment Avenues Are Mutual Funds, Bank Fix Deposits, Equity and Insurance compared to Investmentsin bonds, Gold and Real Estate.